Proyecto De Restructuración De La Empresa Fajas Colombianas Gt Y La Factibilidad Para Incrementar Las Exportaciones De Fajas De Colombia A Ciudad De Guatemala (2023)
In recent years there has been a growing demand for beauty products in Central America, specifically Guatemala where Colombia has played an important role as an exporter. According to the América Central Data page, for the last quarter of 2022, imports to Central America have had an increase of 19%, reaching a ceiling of 156 million dollars, Guatemala being the main buyer of beauty products with 36 million dollars of participation.